PENGARUH TERAPI MUSIK TERHADAP PERKEMBANGAN KEMAMPUAN ANAK DAN REMAJA BERKEBUTUHAN KHUSUS - Saphira Hertha (MANASA, 2017)
Music in many shapes has become something familiar for people in any age. Some people also realize the good effect of music in their life. This effect and function used in music therapy. In music therapy, a therapist uses music and musical activity as tools in therapeutic process. With many program designs to meet client's need, music therapy can be effective for their development. In South East Asia, music therapy is still something new. Information about music therapy is very limited. Music therapy services also only served in certain areas. Furthermore, not many institutions offer education in music therapy field. The aim of this research is to see the effect of music therapy to development of special need children. Methods are survey, field research and evaluation based on music therapy treatment to clients. The result show that music therapy treatment is effective to help special needs children and adolescence. Abstract: Music in many shapes has become something familiar for people in any age. Some people also realize the good effect of music in their life. This effect and function used in music therapy. In music therapy, a therapist uses music and musical activity as tools in therapeutic process. With many program designs to meet client's need, music therapy can be effective for their development. In South East Asia, music therapy is still something new. Information about music therapy is very limited. Music therapy services also only served in certain areas. Furthermore, not many institutions offer education in music therapy field. The aim of this research is to see the effect of music therapy to development of special need children. Methods are survey, field research and evaluation based on music therapy treatment to clients. The result show that music therapy treatment is effective to help special needs children and adolescence.